English: Tingkat Kecemasan Terhadap Tata Bahasa dan Subskala di Kalangan Mahasiswa Bahasa Inggris sebagai Bahasa Asing - Audy Meylinda Mokoginta; Indri Wirahmi Bay; Sri Widyarti Ali (Language Development Center, 2026)
Background: Grammar anxiety is a persistent affective barrier that negatively affects EFL students grammatical performance in higher education settings. Objectives: This study intends to investigate the levels, subscales, and severity of grammar anxiety among fourth-semester EFL students. Method: In this study, a quantitative descriptive design was utilized, with the structured questionnaire serving as the primary source for data collection. The target population consisted of 135 fourth-semester students. However, only 90 students voluntarily participated by completing the questionnaire. Therefore, the study employed a convenience sampling technique. The Grammar Anxiety Scale, which was developed by Ekinci Çelikpazu and Taşdemir, was used as the research instrument. Data analysis was done through descriptive statistics, mean scores, and categorization procedures regarding severity to determine levels and patterns of grammar anxiety. Results and Discussion: It was revealed in the results that 68.89% of the students experience grammar anxiety at a moderate level, 16.67% at a high level, and 14.44% at a low level. The highest anxiety level, among the three subscales, falls into the Emphasis on Grammar Learning subscales, followed by Student Confidence and then Grammar Learning Experience. The researchers concluded that grammar anxiety still remains one of the significant affective factors influencing students' confidence and participation. On the ground of these findings, it is recommended to English teachers to provide a supportive, communicative, and student-centered environment, which may reduce anxiety and enhance student engagement in grammar learning. Conclusions and Implications: This study concludes that grammar anxiety still remains an influential factor in EFL students grammar learning and underlines the need for supportive instructional strategies. From these results, implications have been offered to teachers, curriculum designers, and future researchers on developing approaches that minimize anxiety and enhance grammar learning outcomes.